2009
DOI: 10.1097/ncc.0b013e31819962e0
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Spouses as Informal Caregivers for Recipients of Hematopoietic Stem Cell Transplants

Abstract: Spouses often are the primary caregiver for the hematopoietic stem cell transplant (HSCT) recipients and participate in the transplant recipients' care throughout the HSCT trajectory. The purpose of this qualitative study was to explore and describe the experiences of spouses of HSCT recipients during the acute phase of the transplant trajectory. The participants were spousal caregivers (8 wives and 3 husbands) of transplant recipients. Each participant was interviewed 1 to 6 times. Data were analyzed using Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 34 publications
4
57
2
Order By: Relevance
“…19 n Caregiver Roles Caregivers reported juggling multiple roles, which were categorized and labeled as ''interpreter,'' ''organizer,'' and ''clinician.'' Similar results were found by Wilson and colleagues, 3 who found that the caregiver role often evolved from simply being at the spouse's side to providing emotional support and physical care during the BMT hospitalization. We also noted that the demands of the caregiver role were complicated by the need to ''be strong for everyone'' and often resulted in the caregivers having difficulty in ''finding balance'' in their lives.…”
Section: Positive Growthsupporting
confidence: 77%
See 2 more Smart Citations
“…19 n Caregiver Roles Caregivers reported juggling multiple roles, which were categorized and labeled as ''interpreter,'' ''organizer,'' and ''clinician.'' Similar results were found by Wilson and colleagues, 3 who found that the caregiver role often evolved from simply being at the spouse's side to providing emotional support and physical care during the BMT hospitalization. We also noted that the demands of the caregiver role were complicated by the need to ''be strong for everyone'' and often resulted in the caregivers having difficulty in ''finding balance'' in their lives.…”
Section: Positive Growthsupporting
confidence: 77%
“…14 However, few studies have qualitatively explored the specific challenges of the transplant experience from the perspective of the caregiver, 3,15 and researchers have identified the need for more research to understand the quality of life of caregivers of cancer patients. 16 Stetz and colleagues 15 were among the first researchers to qualitatively explore the needs of caregivers of BMT recipients during treatment.…”
Section: 8y11mentioning
confidence: 99%
See 1 more Smart Citation
“…This made it difficult to make plans-both in the short time and for the future, earlier described (Sabo et al, 2013, Wilson et al, 2009. The uncertainty that arises along the HSCT-trajectory and its effect on the family members has been reported to give a poorer life satisfaction .…”
Section: Discussionmentioning
confidence: 99%
“…", "will the treatment succeed" or "will my partner survive?" Family members have earlier described the HSCT as "riding a roller-coaster in the dark" (Wilson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%